A Percepção de insegurança pelo cidadão confrontada com os gastos com segurança privada - Marreiro, Maria Leonida Soares (2015)
The present dissertation deals with the citizen's expenses with private security, given their perception of insecurity. Considering that violence is part of people’s daily life and that the feeling of not being safe is growing among them, this research presents the issue of violence and its consequences on the expenses that the citizen is forced to bear in order to prevent the risk of being the victim of a crime. The research was carried out using an online questionnaire, which main goal was to identify if there is a relation between the perception of insecurity and the citizen's expenses with private security. The literature review analyzed studies already done about violence and public security expenditures, given that, although it is a current and relevant topic, it also has significant numbers. It has been observed that private security expenses, taking the citizen’s level into consideration, is not adequately investigated yet. Methodologically, a quantitative research of an exploratory nature was carried out. To analyze the data, descriptive and frequency statistics, correlation analysis, univariate regression and factorial analysis were used. The results indicate that the variables studied, inherent to the perception of insecurity by the citizen, did not present significant statistical relation to their expenses, whereas the variables age and family income, according to the profile of the respondents, had a positive association with the citizen's expenses. Finally, the text proposes a categorization of the private security items gotten by the citizen, making it possible to understand the associations between the expenses researched, forming comprehensive components of great explanatory value.